LANGUAGE IN THE DIGITAL AGE: GENRE ANALYSIS OF LINKEDIN PROFILE SUMMARY DISCOURSE - Asyipa Nursani; Tofan Dwi Hardjanto (Esteem Journal of English Education Study Programme, 2024)
This study aims to identify linguistic features in each move and strategy used in LinkedIn profile summaries. The methodology employed is descriptive qualitative research, with data sourced from English-language profile summaries written by Indonesians. The findings reveal a diverse range of linguistic features, all aimed at achieving the communication goals of the profile summary, which include self-promotion, personal branding, and creating a positive image for the reader. These findings are expected to assist LinkedIn users in crafting more attractive and effective profile summaries. The novelty of this research lies in its analysis of contemporary discourse genres that evolve with the times.